PEMBINAAN PUSKESMAS TERHADAP PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH DI WILAYAH KERJA PUSKESMAS PADANG MATINGGI KOTA PADANGSIDIMPUAN - Fitriani Pramita Gurning, SKM., M.Kes; Asni Juliyanthi Daulay (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT The quality of education is closely related to human resources quality as well. Human Resources (HR) is a quality that has physically and mentally healthy. Efforts to develop the human resources quality and healthy among others, by implementing the School Health Unit (UKS). The aim of this study was to determine the PHC Development Program Implementation Effort Against Health at Work Areas Puskemas Matinggi Padang Kota Padangsidempuan 2015. This research uses descriptive research with qualitative analysis using the informant as the subject of the head of the clinic, coordinator UKS, UKS and executive officers UKS of 20 schools in the Work Area Puskemas Matinggi Padang Kota Padangsidempuan 2015 as many as 40 people. The results showed that the distribution of data development at most good health centers (62.5%), but respondents with bad health center development is still high at 37.5% and the distribution of the majority happen UKS implementation (70.0%) and 30.0% did not take place , Data distribution of respondents by fostering health centers in both categories as many as 25 people (62.5%), and poor as many as 15 people (37.5%). Respondent data based on the implementation of the UKS at the elementary school in the working area of Puskesmas Padang Padang city Matinggi Sidimpuan 2015 UKSnya program has been completed by 28 respondents (67.4%) and were not undone UKSnya program as many as 12 respondents (32.6%). The conclusion of this study is that the guidance in the development of health centers have been good and the implementation of UKS have been implemented. Suggested to implementing UKS program in schools in order to further increase knowledge and insight on hygiene Business School program. Keywords: Development, Implementation, UKS